Vehicle tests showing how the weather in autumn influences the wheel–rail traction characteristics. (April 2020) - Meierhofer, Alexander; Trummer, Gerald; Bernsteiner, Christof; Six, Klaus
Train operators report low adhesion in autumn, which they suspect is caused by fallen leaves on a track surrounded by forest and farmland. To investigate and quantify this effect, vehicle tests have been performed in autumn on a track partially surrounded by forest. To also investigate the influence of different weather conditions, the tests were performed on a day with sunny weather and one with high humidity in the morning and drizzle at noon. The results were then compared to other tests and different creep force models from the literature. The results showed a significant influence of the surrounding forest on the traction especially in sunny weather.